Composition, properties, and application of products formed in oxidation of polyethylene by nitric acid - (:unkn) unknown (MAIK NAUKA/INTERPERIODICA/SPRINGER, 2010)
Structure of products formed in polyethylene oxidation by nitric acid was studied by NMR, IR, and electronic absorption spectroscopies and derivatography.